Profil Fungsi Kognitif Berdasarkan Karakteristik Lansia Binaan Sahabat Lansia - Erlina Fazriana (Jurnal Keperawatan Silampari, 2020)
This study aims to determine the cognitive profile based on the characteristics of the elderly assisted my elderly friends in Bandung. This research method is quantitative descriptive research. The results showed that out of 80 elderly respondents, most were in the normal category, as many as 72 elderly (90%). The elderly who are categorized as usual to mild disorders are mostly in the age range of 60-70 years, are female, homemakers work, married marital status, medical history of hypertension and physical activity are homework and gymnastics, while for the elderly with disorders cognitive weight, age 78 years, female gender, widowed, marital status, work as a housewife, medical history of hypertension and physical activity, gymnastics and housework. In conclusion, the cognitive abilities of the elderly assisted my elderly friends in Bandung City in 2019 were mostly in the normal category and the cognitive skills of the elderly with typical to severe types; most of the elderly did homework and gymnastics. Keywords: Elderly Characteristics, Cognitive Ability, Elderly Friends